The Impact of Price and Product Quality on Purchasing Decisions - Darise, Nurul Tritanty; Akbar, Mohammad Aldrin; Lina, Ros (Advances in Business & Industrial Marketing Research, 2025)
Purpose: This study aims to explore the effect of price and product quality on the purchase decision of an automatic motorbike in the study area. Research Design and Methodology: This study employs a quantitative approach, utilizing a survey method through a questionnaire. The study population consists of individuals who use automatic motorbikes in the Entrop area. The sample was collected using the judgment sampling method, with a minimum sample size of 97 respondents. The data were analysed using multiple linear regression to test the simultaneous effect of price and product quality variables on purchasing decisions. Findings and Discussion: The results showed that simultaneously, the price and product quality variables had a significant effect on the decision to purchase an automatic motorbike. Consumers tend to consider a combination of reasonable price and good product quality in making purchasing decisions. This finding confirms that both variables play a significant role in influencing consumer purchasing behavior. This study also supports the consumer value theory and the findings of previous studies, which highlight the importance of product quality and price in purchasing decisions. Implications: The findings of this study have significant practical consequences for companies. Companies should focus on enhancing product quality, driving innovation, and implementing competitive pricing strategies. In addition, companies need to strengthen their brand image and after-sales service to increase customer satisfaction and loyalty. This research also contributes to the realm of science by enhancing the understanding of the interaction between price and product quality in the context of the motorcycle market.